Polchinski ERG Equation in O(N) Scalar Field Theory - Kubyshin, Yuri (2017)
We investigate the Polchinski ERG equation for d-dimensional O(N) scalar field theory. In the context of the non-perturbative derivative expansion we find families of regular solutions and establish their relation with the physical fixed points of the theory. Special emphasis is given to the large N limit for which many properties can be studied analytically.